Recovery-Oriented Nursing for People with Mental Illness - อินจุ้ย รวีวรรณ; ศรีรัตน์ จิราภา; อุไรเลิศ อัจฉรา (Journal of The Royal Thai Army Nurses, 2019)
The recovery concepts in mental health services have been continuous by Changed and development over the past 20 years. Today’s concept of recovery is “recovery orientation” which attempts to move away from traditional concept which based on the bio-medical model. However, the concept of recovery oriented services for people with mental illness is still infancy in Thailand. In this article, is focused on the development of recovery concepts and the impacts of varying concepts on the contemporary recovery oriented care for people with mental illness. Also, the recommendations to improve recovery-oriented practices were identified in this article. The professionals can enhance those strategies to promote the clients’ hope, self-management and sense of belonging in community that can assist people with mental illness to achieve meaningful goals on their own recovery journey.